2015
DOI: 10.1016/j.seizure.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Lacosamide as adjunctive therapy in refractory epilepsy in adults: A systematic review

Abstract: Based on evidence to date, adjunctive lacosamide is a treatment option to reduce seizure frequency in patients with refractory epilepsy and terminate seizures in patients with RSE. The safety information summary can be used to advise patients of potential adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 40 publications
(233 reference statements)
1
14
1
2
Order By: Relevance
“…Responder rates on BRV were comparable to post-marketing experiences with other recently introduced AEDs such as Perampanel (PER; ≥50% responder rate in the largest three trials: 27–50%) or Lacosamide (LCM; ≥50% responder rate: 18–69%). The same did also apply to rates of seizure-free patients (PER: 14–17% in the largest three trials; LCM: 3–33%), as in the present study, 29% were seizure-free with 8.8% being newly seizure-free ( 23 , 24 ).…”
Section: Discussionsupporting
confidence: 52%
“…Responder rates on BRV were comparable to post-marketing experiences with other recently introduced AEDs such as Perampanel (PER; ≥50% responder rate in the largest three trials: 27–50%) or Lacosamide (LCM; ≥50% responder rate: 18–69%). The same did also apply to rates of seizure-free patients (PER: 14–17% in the largest three trials; LCM: 3–33%), as in the present study, 29% were seizure-free with 8.8% being newly seizure-free ( 23 , 24 ).…”
Section: Discussionsupporting
confidence: 52%
“…In regulatory randomized controlled trials conducted in adults, lacosamide has demonstrated to be an effective and safe AED, with 40% of patients with refractory focal epilepsy achieving a 50% reduction in seizure frequency at a short period of time (3 months) [34]. In this review, both retrospective and prospective studies consistently showed efficacy of lacosamide as an add-on therapy in DRE, indicating that the efficacy in children appears to be equivalent to that in adults.…”
Section: Discussionmentioning
confidence: 73%
“…There are only published data regarding the use of levetiracetam (LEV), topiramate (TPM), pregabaline (PGB), lacosamide (LCM) and perampanel (PER) in RSE and SRSE, but these are limited to small case series. 18,24,25 However, there is a good body of evidence favouring the use of other AEDs, such as valproic acid (VPA), phenytoin (PHT) and phenobarbital (PHB), in earlier SE phases. Therefore, if these were started in previous SE phases, it may be legitimate to maintain them in SRSE.…”
Section: Anti-epileptic Drugsmentioning
confidence: 99%